Detention of Food Exported from Indonesia to the USA - Sri Rahardjo (Indonesian Food and Nutrition Progress, 1999)
Agricultural products are expected to survive as export commodities under severe economic crises. Such an expectation could not be fully achieved due to the fact that some Indonesian food commodities exported to USA were held under detention by FDA. The detained food products were mostly cocoa bean, canned tuna, frozen shrimp and fish. Cocoa bean detention was due to the presence of filth and foreign objects, while for frozen shrimp and fish were due to the presence of filth, inadequate sanitary handling, and Salmonella contamination. Detention of canned tuna shipments were due to the presence of filth, decomposition, no accompanying canning schedule process document, or no compliance with the labeling requirements. Especially for cocoa bean export to USA up to present Indonesia has been subjected to automatic detention. Quality management and food safety, against the potential Indonesian export commodities should he improved to he able to compete in global market.